Humans in XAI: Increased Reliance in Decision-Making Under Uncertainty by Using Explanation Strategies - Lammert, Olesja; Richter, Birte; Schütze, Christian; Thommes, Kirsten; Wrede, Britta (Frontiers in Behavioral Economics)

Editorial: ENT | GRENZ | UNGEN (in) der Medienpädagogik - Ade, Larissa; Breiwe, René; Dehmel, Lukas; Wolf, Karsten D.; Rummler, Klaus; Dander, Valentin; Grünberger, Nina; Schiefner-Rohs, Mandy (Zeitschrift MedienPädagogik)

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Multiscale simulation of polymer curing of composites combined mean-field homogenisation methods at large strains - Lenz, Peter; Mahnken, Rolf (International Journal of Solids and Structures)
Keywords: Applied Mathematics; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Carillo Beber, Vinicius; Fernandes, Pedro; Nagel, Christof; Köster, Christian; Matzenmiller, Anton; Hecht, Mathias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Bruchmechanisches Schnittebenenkonzept zur lebensdauergerechten Auslegung von hyperelastischen Klebverbindungen bei multiaxialen und variablen Belastungsamplituden - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson; Buczek, Moritz; Duffe, Tobias; Kullmer, Gunter (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

"Das Berufsfeldpraktikum empfinde ich als nicht notwendig im Studium" - Evaluationsergebnisse zum Berufsfeldpraktikum aus Sicht von Lehramtsstudierenden - Meier, Jana; Vogelsang, Christoph; Rotärmel, Tanja (Das Berufsfeldpraktikum als Professionalisierungselement. Grundlagen, Konzepte, Beispiele für das Lehramtsstudium)

Implementierung eines Algorithmus zur motivbasierten Schnitt-Sparsifizierung - Dorociak, Svitlana

Evaluation of Surrogate Aerosol Experiments to Predict Spreading and Removal of Virus-Laden Aerosols - Beimdiek, Janis; Schmid, Hans-Joachim (Atmosphere)
Keywords: surrogate aerosols; indoor air cleaners; ultra-fine particles; COVID-19; test method; field experiments: clean air delivery rate

Konzeptentwicklung für ein Stahlbatteriegehäuse unter besonderer Berücksichtigung der Fügetechnik und des Korrosionsschutzes - Chudalla, Nick; Schmolke, Tobias; Meschut, Gerson; Spohr, Sebastian; Eckstein, Lutz; Brunner-Schwer, Christian; Rethmeier, Michael; Nothelfer-Richter, Rolf; Hilt, MIchael (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimental and Theoretical Investigation of CO2 Absorption in Aqueous Solution of Glucosamine: Material Property and Equilibrium Data - Hami Dindar, Iman; Mirzaei, Mona; Baumhögger, Elmar; Lutters, Nicole; Kenig, Eugeny Y. (Journal of Chemical & Engineering Data)
Keywords: General Chemical Engineering; General Chemistry

Dynamics of an Absorption/Desorption Plant: Experimental Study and Model Validation - Weber, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

Methodenentwicklung zur Simulation des Viscous Fingering in Klebverbindungen von stahlintensiven Mischbaustrukturen - Al Trjman, Mohamad; Meschut, Gerson; Salten, Alexander Heinrich Johannes; Kenig, Eugeny Y.

New pressure drop and heat transfer correlations for turbulent forced convection in internally channeled tube heat exchanger ducts - Al-Lami, Abbas J.S.; Kenig, Eugeny Y. (Case Studies in Thermal Engineering)
Keywords: Fluid Flow and Transfer Processes; Engineering (miscellaneous)

All you need is love… Gedanken für das neue Jahr - Breckner, Anne

Selbstinszenierungspraktiken als Weg zu Stärkenorientierung, Selbstbestimmung und Teilhabe – eine Kollegiale Weiterbildung für multiprofessionelle Akteursgruppen im (inklusiven) Übergang Schule-Beruf - Kundisch, Heike; Kremer, H.-Hugo; Otto, Franziska (QfI - Qualifizierung für Inklusion Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)

WeGA-WebApp release 4.9.0 - Stadler, Peter; Schmidt, Jakob; Zheng, Xianghua; Ried, Dennis; Richts, Kristina; Schreiter, Solveig; Jakob, Charlene
WeGA-WebApp release 4.9.0 Main features replace external Beacon service #451 update csLink to version v2 #450 Changelog A detailed changelog can be found at https://github.com/Edirom/WeGA-WebApp/wiki/Changelog Full Changelog: v4.8.1...v4.9.0 License This work is available under dual license: BSD 2-Clause and Creative Commons Attribution 4.0 International License (CC BY 4.0)

Edirom/WeGA-ODD: v4.9.0 - Stadler, Peter; Neubert, Anna Maria; Schreiter, Soveig; Obert, Salome; Ried, Dennis

WeGA data package v4.9.0 - Stadler, Peter